16.1k views
1 vote
5-(49/1-5)*2+9-3
what does this equal?

User Florian Bw
by
4.9k points

2 Answers

1 vote

Answer:

the answer is -77 I just looked it up

User Mixologic
by
5.1k points
3 votes
Answer:
-71
Explaining:
5 - (49/1 -5) x2 + 9 - 3
The given expression is solved by using BODMAS rule which means the given expression will be solved in order of: Brackets, of, division, multiplication, addition, and subtraction.
= 5 - (49 -5) x2 + 9 - 3
= 5 - 44 x2 + 9 - 3
= 5 - 88 + 99 - 3
= 5 + 9 - 88 - 3
= 14 - 91
= - 71

User Bitswazsky
by
5.8k points